Explicitations in Literary Translation from Arabic into English with specific reference to Khalil Gibran’s Ḥadīqat Al- Nabī - El Kanany, Toufic Abdo Said Mohamed; Al Suwaidi, Balqees Saif; Mansour, Arwa (Journal of Humanities & Social Sciences, 2018)
This study aimed to test Blum- Kulka’s (1986) hypothesis that explicitation is a translation universal. In other words, the study aims to examine the general tendency in translation studies that translated texts are more explicit than source texts or non- translated texts in the same language. The study’s significance stems from the fact that it is one of few studies that investigate the explicitation hypothesis with specific reference to literary translation from English into Arabic. To be more specific, Gibran’s حديقة النبي or The Garden of the Prophet has been used to test the validity of the hypothesis in Arabic. We are aware that the hypothesis has been tested with reference to a considerable number of languages such as German, English, Persian, etc. The paper has concluded that explicitations are found in the Arabic translated texts at the grammatical, lexical, pragmatic and translation- inherent levels.